Understanding the Impact of Exploration-Exploitation Dilemma and External Factors on Business Growth: A Case Study of PT Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk (BJB) Branch in Coblong - Ayesha, Ivonne (Takaza Innovatix Labs Ltd., 2024)
The study examines the impact of Exploration Level, Exploitation Level, and External Factors on Business Growth at PT Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk (BJB) Branch in Coblong. Through regression analysis, the results reveal significant effects of these factors on Business Growth. Exploration and Exploitation Levels exhibit substantial positive impacts, emphasizing the significance of innovation and effective utilization of existing resources. Additionally, External Factors demonstrate a robust influence, emphasizing the need for adaptability to external dynamics. The collective impact of these variables significantly contributes to understanding Business Growth, as supported by a well-fitted regression model. This study underscores the importance of strategic adaptability, innovation, and responsive management to external changes for sustainable business growth. The findings provide valuable insights for management, guiding the formulation of adaptive strategies to foster innovation, optimize resource utilization, and navigate external dynamics for enduring business success at BJB Coblong.